BACTERIAL PROFILE AND ANTIBIOGRAM OF OTITIS MEDIA AMONG CHILDREN IN YEMEN - Bin Mohanna, Mabrook Aidah; Bahannan, Abdulrahman Ali (Journal of Ayub Medical College Abbottabad, 2016)
Background: Otitis media is a worldwide disease and is higher in developing countries, particularly among the low socioeconomic levels of the society. The aim of the study is to identify the bacterial etiologic agents of otitis media (OM) and their antibiotics sensitivity patterns among children in Specialized Sam Paediatric Centre (SSPC) and Al-Mamoon Diagnostic Medical Centre (AMDC), in Sana’a city. Methods: A cross-sectional study was done in SSPC and AMDC from January to October 2015. A total of 150 patients who had ear pus discharge and clinically diagnosed as OM were included in this study. Samples of ear discharge were collected, bacteriologically tested by standard methods and bacterial strains were identified using biochemical testes. Questionnaire was administered on patients or parents that cover the age, gender and the duration of symptoms. Results: A total of 150 children with OM, their age ranged from below 1-15 years (85 males and 65 females). Children less than 5 years of age were 100 and 50 with age ranged from 6-15 years. Bacterial isolates were Staphylococcus aureus (44%), Pseudomonas aeruginosa (12.67%), Enterococcus species (12.67%), and Streptococcus pneumonia (10%). Bacterial culture revealed that, Staphylococcus aureus sensitivity to cefotaxime and azithromycin was 98%, to amoxicillin-clavulanic acid was 92% and it was 85% to gentamicin. Pseudomonas aeruginosa sensitivity to cefotaxime was 100%, to azithromycin and gentamicin was 98% and it was 80% to cefaclor. Enterococcus sensitivity to amoxicillin-clavulanic acid was 85%, to azithromycin was 80%, and it was 75% to cefotaxime, and gentamicin. Conclusion: The most common microorganism isolated was Staphylococcus aureus followed by Pseudomonas, Enterococcus species, and then Streptococcus pneumonia. The most effective antibiotics were cefotaxime, amoxicillin-clavulanic acid, azithromycin and gentamicin. Therefore, knowledge of antimicrobial susceptibility test is essential for guiding appropriate antibacterial therapy. Keywords: Otitis media; Bacterial isolates; Antibiotic sensitivity; Children